2014
DOI: 10.5214/ans.0972.7531.210403
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor in children with Autism Spectrum Disorder

Abstract: BackgroundAutism Spectrum Disorder (ASD) is a complex neurobehavioral syndrome with no known biomarker so far for early detection. It has been challenging, both to classify typical autism and associate a suitable biomarker with clinical phenotype spectrum. Brain-derived neurotrophic factor (BDNF) has emerged as a key neurotrophin regulating synaptic plasticity, neuronal differentiation and survival.PurposeRecently, BDNF depletion is reported in neurodegenerative as well as in psychiatric disorders, associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 33 publications
2
38
0
2
Order By: Relevance
“…BDNF is involved in activity-dependent synaptic plasticity and there have been a number of studies linking BDNF with ASD (Armeanu, Mokkonen, & Crespi, 2017;Bryn et al, 2015;Kasarpalkar, Kothari, & Dave, 2014;Saghazadeh & Rezaei, 2017;Wang et al, 2015). Within the context of a genetic predisposition for ASD, coupled with environmental factors that result in over excitation of neurons, BDNF levels increase dramatically, resulting in the presence of a fatty coating around the neurons and megalencephaly (Merzenich, Van Vleet, Nahum, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is involved in activity-dependent synaptic plasticity and there have been a number of studies linking BDNF with ASD (Armeanu, Mokkonen, & Crespi, 2017;Bryn et al, 2015;Kasarpalkar, Kothari, & Dave, 2014;Saghazadeh & Rezaei, 2017;Wang et al, 2015). Within the context of a genetic predisposition for ASD, coupled with environmental factors that result in over excitation of neurons, BDNF levels increase dramatically, resulting in the presence of a fatty coating around the neurons and megalencephaly (Merzenich, Van Vleet, Nahum, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is a neurotrophic factor related to neuronal maturation and synaptic synthesis. BDNF is elevated in children with ASD [Bryn et al, ; Kasarpalkar et al, ; Zhang et al, ] and genes associated with neurodevelopmental disorders impact BDNF expression [Briz et al, ; Koh, Lim, Byun,& Yoo, ; Louhivuori et al, ; Ouyang et al, ]. Prenatal exposure to other environmental toxins impact BDNF: Bisphenol A altered DNA methylation in mice [Kundakovic et al, 2014] and valproate increased BDNF mRNA and protein levels in mice and rats [Almeida, Roby, & Krueger, ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [150][151][152] , which have not all been replicated 153 , have reported an increase in BDNF levels in the blood of patients with ASD. In addition, high plasma levels of serotonin and N-acetylserotonin, as well as low plasma levels of melatonin, are more frequently observed in individuals with ASD than in controls 154,155 .…”
Section: Synaptic Homeostasis and Asdsmentioning
confidence: 99%